Comparing Journal Use Between Biology Faculty and Undergraduate Students - Joseph R. Kraus (Issues in Science and Technology Librarianship)
From 1997 through 200: the faculty in the Biological Sciences Department at the University of Denver wrote 90 articles that were indexed by Thomson/ISI's Science Citation Index. Using data from this database, a list of the sources cited by the faculty was prepared. There were a total of :942 citations, and most of those citations were to journal articles. The top cited journal list was compared to a list of journals our biology students used. Many of the journals in the top 20 were co-listed, but for less cited journals, the faculty used many other journals for their research. [ABSTRACT FROM AUTHOR]